The Cyclin B2/CDK1 Complex Conservatively Inhibits Separase Activity in Oocyte Meiosis II - Li, Jian; Zhang, Hong-Yong; Wang, Feng; Sun, Qing-Yuan; Qian, Wei-Ping (Frontiers in Cell and Developmental Biology, 2021)
Recently we have reported that the cyclin B2/CDK1 complex regulates homologous chromosome segregation through inhibiting separase activity in oocyte meiosis I, which further elucidates the compensation of Cyclin B2 on Cyclin B1’s function in meiosis I. However, whether cyclin B2/CDK1 complex also negatively regulates separase activity during oocyte meiosis II remains unknown. In the present study, we investigated the function of cyclin B2 in meiosis II of oocyte. We found that stable cyclin B2 expression impeded segregation of sister chromatids after oocyte parthenogenetic activation. Consistently, stable cyclin B2 inhibited separase activation, while introduction of non-phosphorylatable separase mutant rescued chromatid separation in the stable cyclin B2-expressed oocytes. Therefore, the cyclin B2/CDK1 complex conservatively regulates separase activity via inhibitory phosphorylation of separase in both meiosis I and meiosis II of mouse oocyte.